2011
DOI: 10.1128/jb.01123-10
|View full text |Cite
|
Sign up to set email alerts
|

Translation Efficiency of Antiterminator Proteins Is a Determinant for the Difference in Glucose Repression of Two β-Glucoside Phosphotransferase System Gene Clusters inCorynebacterium glutamicumR

Abstract: Corynebacterium glutamicum R has two ␤-glucoside phosphoenolpyruvate, carbohydrate phosphotransferase systems (PTS) encoded by bglF and bglF2 located in the respective clusters, bglF-bglA-bglG and bglF2-bglA2-bglG2. Previously, we reported that whereas ␤-glucoside-dependent induction of bglF is strongly repressed by glucose, glucose repression of bglF2 is very weak. Here, we reveal the mechanism behind the different effects of glucose on the two bgl genes. Deletion of the ribonucleic antiterminator sequence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Although most PTS are specific for a particular carbohydrate, it has previously been described that PTS permeases transport two or more structurally related β-glucosides (Le Coq et al, 1995;Deutscher et al, 2006;Tanaka et al, 2011). While studying the metabolism of other mucosal associated glycans in L. casei we showed that fucosyl-α1,3-GlcNAc is transported by a specific PTS in a phosphorylation-independent manner before being intracellularly hydrolysed by an α-L-fucosidase (Rodriguez-Diaz et al, 2012a).…”
Section: Discussionmentioning
confidence: 95%
“…Although most PTS are specific for a particular carbohydrate, it has previously been described that PTS permeases transport two or more structurally related β-glucosides (Le Coq et al, 1995;Deutscher et al, 2006;Tanaka et al, 2011). While studying the metabolism of other mucosal associated glycans in L. casei we showed that fucosyl-α1,3-GlcNAc is transported by a specific PTS in a phosphorylation-independent manner before being intracellularly hydrolysed by an α-L-fucosidase (Rodriguez-Diaz et al, 2012a).…”
Section: Discussionmentioning
confidence: 95%
“…2). Genome sequencing also revealed that the bglF gene was located in the cluster bglFbglA-bglG, which has previously been identified as the β-glucoside utilization system in another wild-type C. glutamicum R (Kotrba et al 2003;Tanaka et al 2009Tanaka et al , 2011. Interestingly, a search for C. glutamicum genome databases revealed that the bglF-bglA-bglG DNA region including the upstream mutation site was missing from the corresponding position in the genome of C. glutamicum R and ATCC 13032 (Fig.…”
Section: Identification Of the Suppressor Mutation In Strain Sph1mentioning
confidence: 91%
“…Disruption of any of the genes in strain ATCC 13032 results in a phenotype exhibiting little growth on glucose (Parche et al 2001). Exceptionally, another wildtype strain C. glutamicum R can consume glucose not only via the glucose-PTS but also via the β-glucoside-PTS because C. glutamicum R, unlike C. glutamicum ATCC 13032, has two sets of β-glucoside-PTSs that are redundantly responsible for the uptake of the β-glucosides, such as salicin and arbutin, and also glucose (Kotrba et al 2003;Tanaka et al 2009Tanaka et al , 2011.…”
Section: Introductionmentioning
confidence: 98%
“…Decreased glucose utilization may relieve the catabolite repression by glucose. For example, bglF-bglA-bglG genes, coding for the ␤-glucoside catabolic genes, are under strict control of glucose repression (20). Therefore, increased expression of the bglF-bglA-bglG genes may be the result of weakened glucose repression.…”
Section: Discussionmentioning
confidence: 99%